Heavy metals species affect fungal-bacterial synergism during the bioremediation of fluoranthene (2016)
The co-occurrence of polycyclic aromatic hydrocarbons (PAHs) with heavy metals (HMs) is very common in contaminated soils, but the influence of HMs on fungal-bacterial synergism during PAH bioremediation has not been investigated. The bioremediation of fluoranthene-contaminated sand using co-cultures of Acremonium sp. P0997 and Bacillus subtilis showed increases of 109.4 and 9.8 % in degradation compared to pure bacterial and fungal cultures, respectively, removing 64.1 ± 1.4 % fluoanthene in total. The presence of Cu2+ reduced fluoranthene removal to 53.7 ± 1.7 %, while inhibiting bacterial growth, and reducing translocation of bacteria on fungal hyphae by 49.5 %, in terms of the bacterial translocation ratio. Cu2+ reduced bacterial diffusion by 46.8 and 31.9 %, as reflected by D (a bulk random motility diffusional coefficient) and Deff (the effective one-dimensional diffusion coefficient) compared to the control without HM supplementation, respectively. However, Mn2+ resulted in a 78.2 ± 1.9 % fluoranthene degradation, representing an increase of 21.9 %, while enhancing bacterial growth and bacterial translocation on fungal hyphae, showing a 12.0 % increase in translocation ratio, with no observable impact on D and Deff. Hence, the presence of HMs has been shown to affect fungal-bacterial synergism in PAH degradation, and this effect differs with HM species. © 2016, Springer-Verlag Berlin Heidelberg.